KONTRIBUSI KECERDASAN EMOSIONAL DAN SPIRITUAL TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDS IT SAINS INSANI TANJUNG MORAWA - Khairul Ameer; Afrahul Fadhila Daulay; Humaida Br Hasibuan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the contribution of emotional and spiritual intelligence to students' learning motivation in the Islamic Religious Education learning subject at SDS IT Insani Science Tanjung Morawa. The research sample involved 40 students. The method used in the research is quantitative research. Based on the research results it is found that 1) there is a significant contribution between emotional intelligence on students’ learning motivation of Islamic Religious Education learning subject at SDS IT Insani Science Tanjung Morawa. If students have the right emotional intelligence, this would make a positive contribution to students’ learning motivation. In addition, 2) there is a significant contribution between spiritual intelligence on students’ learning motivation in Islamic Religious Education learning subjects at SDS IT Insani Science Tanjung Morawa. The better spiritual intelligence is, the more it produces positive contributions to students’ learning motivation. 3) There is a significant contribution between emotional intelligence and spiritual intelligence simultaneously to students’ learning motivation at SDS IT Insani Science Tanjung Morawa. Thus, good emotional intelligence and spiritual intelligence can provide a contribution to students’ learning motivation.